![image](https://tex.z-dn.net/?f=a_2%2Ba_4%2Ba_6+%3D18%5C+%3D%3E+%28a_1%2Bd%29%2B%28a_1%2B3d%29%2B%28a_1%2B5d%29%3D18%5C+%3D%3E%5C%5C%0A3a_1%2B9d%3D18%5C+%3D%3E+a_1%2B3d%3D6%5C+%3D%3E+a_4%3D6%5C+%3D%3E+a_2%2Ba_6%3D12.%5C%5C%5C%5C%0Aa_2%2Aa_4%2Aa_6%3D168%5C+%3D%3E+a_2%2A6%2Aa_6%3D168%5C+%3D%3E+a_2%2Aa_6%3D28.)
(a_1+d)+(a_1+3d)+(a_1+5d)=18\ =>\\
3a_1+9d=18\ => a_1+3d=6\ => a_4=6\ => a_2+a_6=12.\\\\
a_2*a_4*a_6=168\ => a_2*6*a_6=168\ => a_2*a_6=28." alt="a_2+a_4+a_6 =18\ => (a_1+d)+(a_1+3d)+(a_1+5d)=18\ =>\\
3a_1+9d=18\ => a_1+3d=6\ => a_4=6\ => a_2+a_6=12.\\\\
a_2*a_4*a_6=168\ => a_2*6*a_6=168\ => a_2*a_6=28." align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+%5Cbegin%7Bcases%7D+a_2%2Ba_6%3D12+%5C%5C+a_2%2Aa_6%3D28+%5Cend%7Bcases%7D+%3C%3D%3E++%5Cbegin%7Bcases%7D+a_2+%3D12-a_6+%5C%5C+%2812-a_6%29%2Aa_6%3D28+%5Cend%7Bcases%7D+%3D%3E%5C%5C%0A%28a_6%29%5E2-12a_6%2B28%3D0%5C%5C%0Aa_6%3D6%D0%B12%5Csqrt2%5C%5C%0A1%29+a_6%3D6-2%5Csqrt2+%5C+%3D%3Ea_2%3D6%2B2%5Csqrt2%5C+%3D%3E+d%3D%5Cfrac%7Ba_4-a_2%7D%7B2%7D%3D%5C%5C%0A%3D%5Cfrac%7B6-6-2%5Csqrt2%7D%7B2%7D%3D-%5Csqrt2%5C+%3D%3E+a_1%3Da_2-d%3D6%2B2%5Csqrt2%2B%5Csqrt2%3D%5C%5C+%0A%3D6%2B3%5Csqrt2%3B+%5C%5C%0A2%29+a_6%3D6%2B2%5Csqrt2+%5C+%3D%3Ea_2%3D6-2%5Csqrt2%5C+%3D%3E+d%3D%5Cfrac%7B6-6%2B2%5Csqrt2%7D%7B2%7D%3D%5C%5C%3D%5Csqrt2%5C+%3D%3E++a_1%3Da_2-d%3D6-2%5Csqrt2-%5Csqrt2%3D%5C%5C+%0A%3D6-3%5Csqrt2.%5C%5C%5C%5C%0AOmbem%3A%5C+a_1%3D6%D0%B13%5Csqrt2.)
\begin{cases} a_2 =12-a_6 \\ (12-a_6)*a_6=28 \end{cases} =>\\
(a_6)^2-12a_6+28=0\\
a_6=6б2\sqrt2\\
1) a_6=6-2\sqrt2 \ =>a_2=6+2\sqrt2\ => d=\frac{a_4-a_2}{2}=\\
=\frac{6-6-2\sqrt2}{2}=-\sqrt2\ => a_1=a_2-d=6+2\sqrt2+\sqrt2=\\
=6+3\sqrt2; \\
2) a_6=6+2\sqrt2 \ =>a_2=6-2\sqrt2\ => d=\frac{6-6+2\sqrt2}{2}=\\=\sqrt2\ => a_1=a_2-d=6-2\sqrt2-\sqrt2=\\
=6-3\sqrt2.\\\\
Ombem:\ a_1=6б3\sqrt2." alt=" \begin{cases} a_2+a_6=12 \\ a_2*a_6=28 \end{cases} <=> \begin{cases} a_2 =12-a_6 \\ (12-a_6)*a_6=28 \end{cases} =>\\
(a_6)^2-12a_6+28=0\\
a_6=6б2\sqrt2\\
1) a_6=6-2\sqrt2 \ =>a_2=6+2\sqrt2\ => d=\frac{a_4-a_2}{2}=\\
=\frac{6-6-2\sqrt2}{2}=-\sqrt2\ => a_1=a_2-d=6+2\sqrt2+\sqrt2=\\
=6+3\sqrt2; \\
2) a_6=6+2\sqrt2 \ =>a_2=6-2\sqrt2\ => d=\frac{6-6+2\sqrt2}{2}=\\=\sqrt2\ => a_1=a_2-d=6-2\sqrt2-\sqrt2=\\
=6-3\sqrt2.\\\\
Ombem:\ a_1=6б3\sqrt2." align="absmiddle" class="latex-formula">